2022
DOI: 10.1039/d2mh00338d
|View full text |Cite
|
Sign up to set email alerts
|

Rational mechanochemical design of Diels–Alder crosslinked biocompatible hydrogels with enhanced properties

Abstract: An important but often overlooked feature of Diels–Alder (DA) cycloadditions is the ability for DA adducts to undergo mechanically induced cycloreversion when placed under force. Herein, we demonstrate that the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…However, some experimental results show different crack morphologies, like ring-shaped cracks, 14,28,29 conical cracks, 15 or more complex morphologies. 30 In these scenarios, our prediction could be inaccurate, and one would have to extend our model to account for complex crack morphologies. We leave this for future work.…”
Section: Resultsmentioning
confidence: 99%
“…However, some experimental results show different crack morphologies, like ring-shaped cracks, 14,28,29 conical cracks, 15 or more complex morphologies. 30 In these scenarios, our prediction could be inaccurate, and one would have to extend our model to account for complex crack morphologies. We leave this for future work.…”
Section: Resultsmentioning
confidence: 99%
“…Recent literature has reported that Diels–Alder adducts undergo mechanically induced cycloreversion when loading a mechanical force [ 62 , 63 ]. Through rational computational design, “mechanoresistant” Diels–Alder adducts were identified by constrained geometries simulating external force models and employed to enhance failure strength of crosslinked hydrogels [ 64 ].…”
Section: Dynamic Covalent Chemistrymentioning
confidence: 99%
“…Representative examples include mechanochromic molecules, which change material color or luminescence through mechanochemical transformations, 2,4 and the controlled scission or extension of stress-bearing mechanophores that directly impact the tearing or stretching of the networks into which they are incorporated. [22][23][24] By indirect pathways, we refer to systems in which initial mechanochemical responses generate species that go on to react in a way that has macroscopic consequences. For example, the mechanochemical generation of protons, [25][26][27] radicals, 10 catalysts, 28 or reactive ene structures 12 can be coupled to polymerization/crosslinking reactions [10][11][12] or color changes brought about by subsequent acid-base reactions.…”
Section: Introductionmentioning
confidence: 99%